Research Priorities for Achieving Healthy Marine Ecosystems and Human Communities in a Changing Climate - Friedman, Whitney R.; Halpern, Benjamin S.; McLeod, Elizabeth; Beck, Michael W.; Duarte, Carlos M.; Kappel, Carrie V.; Levine, Arielle; Sluka, Robert D.; Adler, Steven; O’Hara, Casey C.; Sterling, Eleanor J.; Tapia-Lewin, Sebastian; et al. (Frontiers in Marine Science, 2020)
The health of coastal human communities and marine ecosystems are at risk from a host of anthropogenic stressors, in particular, climate change. Because ecological health and human well-being are inextricably connected, effective and positive responses to current risks require multidisciplinary solutions. Yet, the complexity of coupled social-ecological systems has left many potential solutions unidentified or insufficiently explored. The urgent need to achieve positive social and ecological outcomes across local and global scales necessitates rapid and targeted multidisciplinary research to identify solutions that have the greatest chance of promoting benefits for both people and nature. To address these challenges, we conducted a forecasting exercise with a diverse, multidisciplinary team to identify priority research questions needed to promote sustainable and just marine social-ecological systems now and into the future, within the context of climate change and population growth. In contrast to the traditional reactive cycle of science and management, we aimed to generate questions that focus on what we need to know, before we need to know it. Participants were presented with the question, "If we were managing oceans in 2050 and looking back, what research, primary or synthetic, would wish we had invested in today?" We first identified major social and ecological events over the past 60 years that shaped current human relationships with coasts and oceans. We then used a modified Delphi approach to identify nine priority research areas and 46 questions focused on increasing sustainability and well-being in marine social-ecological systems. The research areas we identified include relationships between ecological and human health, access to resources, equity, governance, economics, resilience, and technology. Most questions require increased collaboration across traditionally distinct disciplines and sectors for successful study and implementation. By identifying these questions, we hope to facilitate the discourse, research, and policies needed to rapidly promote healthy marine ecosystems and the human communities that depend upon them.